Meal regularity is associated with self-esteem among grade 5 children. Issue 2 (9th December 2020) - Eckert, Katherine F; Asbridge, Mark; Campbell, Leslie Anne; Stewart, Sam; Bennett, Mark; Loewen, Olivia K; Veugelers, Paul J; Cahill, Leah E
ABSTRACT: Background: Meal regularity is associated with many aspects of mental health. However, few studies have examined whether a relationship exists between meal regularity and self-esteem in children. Objectives: The objective of this study was to determine whether an association exists between meal regularity and self-esteem in grade 5 children. Methods: Among 4009 grade 5 students (mean age = 11.0 years ± SEM = 0.006) from the 2011 Children's Lifestyle and School Performance Study (CLASS-II; Nova Scotia, Canada), cross-sectional meal regularity survey data (family supper, supper in front of the television, supper alone, skipping breakfast, and skipping lunch) were collected using the Harvard Youth/Adolescent Food Frequency Questionnaire and examined in relation to self-esteem. Multilevel mixed-effects logistic regression was used to determine the ORs and 95% CIs associated with low self-esteem. Analyses were stratified by sex and adjusted for sociodemographic and lifestyle covariates. Results: Compared to children who ate supper in front of the television or alone either never or less than once/week, children had greater odds of low self-esteem if 5 or more times/week they ate supper in front of the television (OR = 1.85; 95% CI, 1.40−2.43) or alone (OR = 4.23; 95% CI, 2.58−6.95). Compared to children who ate family supper 5 or more times/week, children who ate family supper never or less than once/week had greater odds of low self-esteem (OR: 1.97; 95% CI, 1.51−2.56). Skipping breakfast and skipping lunch were associated with greater odds of low self-esteem [OR = 2.92 (95% CI, 1.87−4.57) and OR = 4.82 (95% CI, 2.14−10.87) respectively]. Conclusions: In our study of grade 5 children, all 5 indicators of meal regularity tested are significantly and consistently associated with self-esteem.